Characterization of ankle dorsiflexors performance in healthy subjects following maximal-intensity isokinetic resistance training. Issue 5 (October 2015) - Manca, A.; Solinas, G.; Dragone, D.; Dvir, Z.; Deriu, F.
Abstract The purpose of this randomized trial was to examine, in healthy subjects, the effect of unilateral isokinetic–concentric training of the dominant ankle dorsiflexors (DF) on the peak moment (PM), mean PM (MPM), maximal work and mean work (meanW). Thirty volunteers (26.7 ± 4.6 years old) underwent bilateral isokinetic testing of ankle DF at 45 and 90°/s. Participants were randomly assigned to a control or a training group. The training lasted 4 weeks (4-day/week). All dynamometric parameters increased significantly only in the training group for the trained leg (p < 0.05), with greater gains in work (32–47% at 45°/s and 31–41% at 90°/s) than moment variables (14–18% at 45°/s and 14–28% at 90°/s). Similar increases in strength were also noted at both angular velocities in the untrained leg (p < 0.01) for both work and moment parameters, depicting a cross-training effect. Correlations between 'moments' and 'works' increased in both legs after training from 0.59–0.77 to 0.79–0.95. Principal component analysis indicated that, at baseline, PM showed the highest weight on DF performance; after training, meanW at 90°/s and MPM at 45°/s exhibited the highest loadings. High-intensity training of ankle DF increase the ability in generating energy throughout the entire range of motion rather than maximizing the PM.